2013
DOI: 10.1186/2047-0525-2-21
|View full text |Cite
|
Sign up to set email alerts
|

Serum arterial lactate concentration predicts mortality and organ dysfunction following liver resection

Abstract: BackgroundThe aim of this study was to determine if the post-operative serum arterial lactate concentration is associated with mortality, length of hospital stay or complications following hepatic resection.MethodsSerum lactate concentration was recorded at the end of liver resection in a consecutive series of 488 patients over a seven-year period. Liver function, coagulation and electrolyte tests were performed post-operatively. Renal dysfunction was defined as a creatinine rise of >1.5x the pre-operative val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 47 publications
4
35
1
Order By: Relevance
“…14,15 Although methodologically criticizable (retrospective single-center review of only 151 patients, OR and 95% CI not provided, cutoff for lactate concentration not reported), the study by Watanabe et al 14 was the first to suggest an association between initial lactate concentration and mortality following hepatectomy, with an AUROC close to that found in the present study. In the study by Wiggans et al, 15 the cutoff for lactate concentration above which morbidity and mortality were significantly higher was twice that in the present study (6 mmol/L), but was selected arbitrarily rather than determined by sensitivity analysis. In addition, no multivariable analysis was performed to test for potential confounders in that study.…”
Section: Interpretation With Reference To Other Studiessupporting
confidence: 68%
See 1 more Smart Citation
“…14,15 Although methodologically criticizable (retrospective single-center review of only 151 patients, OR and 95% CI not provided, cutoff for lactate concentration not reported), the study by Watanabe et al 14 was the first to suggest an association between initial lactate concentration and mortality following hepatectomy, with an AUROC close to that found in the present study. In the study by Wiggans et al, 15 the cutoff for lactate concentration above which morbidity and mortality were significantly higher was twice that in the present study (6 mmol/L), but was selected arbitrarily rather than determined by sensitivity analysis. In addition, no multivariable analysis was performed to test for potential confounders in that study.…”
Section: Interpretation With Reference To Other Studiessupporting
confidence: 68%
“…26 In the present study, diabetes was the only preoperative predictor of increased LCT-EOS concentration, as has been shown by others. 15 Diabetes is associated with impaired lactate metabolism via gluconeogenesis. 27 The role of diabetes in exacerbating liver damage following inflow occlusion has been suggested previously in a series of patients with nonalcoholic steatohepatitis undergoing liver resection.…”
Section: Interpretation With Reference To Other Studiesmentioning
confidence: 99%
“…In patients undergoing coronary artery bypass graft, metabolic acidosis correlated with increased length of stay in the ICU . Increased serum lactate after liver resection has been associated with increased length of stay, probability of complications—including leak, hyperbilirubinemia, and abscess formation—and mortality . In the transplant literature, metabolic acidosis correlates with increased risk of renal allograft futility (defined as patient death or need for renal replacement therapy at 3 months post‐simultaneous liver‐kidney transplant) 18 as well as increased need for damage control surgery (defined by intra‐abdominal packing and delayed reconstruction) .…”
Section: Discussionmentioning
confidence: 99%
“…Warm ischemia and subsequent ischemiareperfusion in the liver cells induced by PTC can increase the serum lactate concentration [10][11][12]. Studies have shown that when the serum lactate concentration is > 6 mmol/L after liver resection, the 90-day postoperative mortality rate increases significantly to 28%; however, the mortality rate is only 0.7% when the serum lactate concentration is < 2 mmol/L [16].…”
Section: Introductionmentioning
confidence: 99%